How Law Affects Lending - Haselmann, Rainer; Pistor, Katharina; Vig, Vikrant (Review of Financial Studies, 2010)
The paper explores how legal change affects lending behavior of banks in twelve transition economies of Central and Eastern Europe. In contrast to previous studies, we use bank level rather than aggregate data, which allows us to control for country level heterogeneity and analyze the effect of legal change on different types of lenders. Using a differences-in-differences methodology to analyze the within country variation of changes in creditor rights protection, we find that the credit supplied by banks increases subsequent to legal change. Further, we show that collateral law matters more for credit market development than bankruptcy law. We also show that entrants respond more strongly to legal change than incumbents. In particular, foreign-owned banks extend their lending volume substantially more than do domestic banks, be they private or state owned. The same holds when we use foreign greenfield banks as proxies for new entrants. These results are robust after controlling for a wide variety of possibilities.